End of Meeting Report - ISPC 6 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2012)
The sixth ISPC meeting was attended by 36 participants from 26th to 28th September 2012. The report annexes contain the list of participants as well as the final agenda for the meeting. A field trip towards Jeldu (site of an ILRI/IWMI project) was organized on 29th September 2012.